2016
DOI: 10.1007/978-3-319-27006-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Risk Communication and the Role of the Public: Towards Inclusive Environmental Governance of the Baltic Sea?

Abstract: This chapter focuses on forms of and challenges for risk communication within regional environmental governance, based on an analysis of fi ve environmental risks in the Baltic Sea -marine oil transportation, chemicals, overfi shing, eutrophication and alien species. We address questions about how risks are framed and communicated and also analyse the role of communication in the governance process. Our main focus is on risk communication with the public (e.g. existing institutional arrangements and procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…And in general, there is a fairly big gap between ideal scenarios and practice when it comes to broad stakeholder participation and communication of environmental risk governance of the Baltic Sea (including the EU level) (Dreyer et al 2011(Dreyer et al , 2014Jönsson et al 2016 ;. From the case studies, we found scant evidence of real refl ection on and practice of participatory and communication activities.…”
Section: Multi-actormentioning
confidence: 85%
See 2 more Smart Citations
“…And in general, there is a fairly big gap between ideal scenarios and practice when it comes to broad stakeholder participation and communication of environmental risk governance of the Baltic Sea (including the EU level) (Dreyer et al 2011(Dreyer et al , 2014Jönsson et al 2016 ;. From the case studies, we found scant evidence of real refl ection on and practice of participatory and communication activities.…”
Section: Multi-actormentioning
confidence: 85%
“…Moreover, the need for transdisciplinary knowledge production, as well as co-production of knowledge among various types of knowledge holders needs to be acknowledged (Kemp and Loorbach 2006 ). Stakeholder inclusion is generally seen as a necessary element in refl exive governance (see also Jönsson et al 2016 ). Different actors can shed additional light on common problems.…”
Section: Multi-actormentioning
confidence: 99%
See 1 more Smart Citation
“…Since two-way communication does not exclude oneway communication, one-way information is still predominant in the cross-national discussion of environmental public risk communication (Jönsson et al 2016). This form of risk communication is identifiable in wildfire warning systems, lectures, brochures, and news releases that aim to promote public awareness of risk.…”
Section: Main Forms Of Risk Communicationmentioning
confidence: 99%
“…The academic literature also discusses instrumental reasons for inclusiveness (e.g. Boström 2006 ;Jönsson et al 2016 ). For example, it has been argued that inclusiveness generates new and more socially robust knowledge, stimulates mutual learning and ultimately facilitates capacity building in environmental governance.…”
Section: Stakeholder Participation and Communicationmentioning
confidence: 99%